Microinjection of pruritogens in NGF-sensitized human skin - Solinski, Hans Jürgen; Rukwied, Roman; Schmelz, Martin (Scientific reports, 2021)
Single intradermal injections of nerve growth factor (NGF) evoke prolonged but temporally distinct sensitization patterns to somatosensory stimuli. Focal administration of the non-histaminergic pruritogen cowhage but not histamine resulted in elevated itch at day 21 after NGF administration. Here, we injected bovine adrenal medulla peptide 8-22 (BAM8-22), β-alanine (β-ALA) and endothelin-1 (ET-1) into NGF-treated skin of 11 healthy volunteers and investigated the corresponding itch/pain and flare reactions. β-ALA was the weakest pruritogen, while BAM8-22 and ET-1 were equally potent as histamine. NGF did not sensitize itch or flare reactions induced by any compound, but injection and evoked pain were increased at day 21 and 49. The involvement of histamine H1 receptors in itch was explored in eight subjects after oral cetirizine. ET-1-induced itch and flare were significantly reduced. BAM8-22 and β-ALA itch were not affected, but flare responses after BAM8-22 reduced by 50%. The results indicate that a single NGF injection does not sensitize for experimentally induced itch but increases pain upon pruritogen injection. In healthy humans, pruritic and algetic processing appear differentially regulated by NGF. However, in patients suffering chronic itch, prolonged elevation of NGF-levels under inflammatory conditions may contribute to elevated itch.
Gesehen am 04.01.2023